Effectiveness of Family Therapy in Social Work Practice in Buhara Sub-County Kabale District. - Tukamushaba, Vian (Kabale University, 2024)
The study sought to evaluate the effectiveness of family therapy in social work practice in Kabale District, Uganda. The study was guided by the following objectives namely; to identify the activities involved in family therapy in social work practice in Buhara Sub County, to find out the challenges faced by social workers in family therapy in Buhara Sub County, and to assess the strategies for improving social work practice in Buhara Sub County. The study sampled 50 respondents from the target population of 56. The study used a descriptive research design combined with a case study design. The findings/ results showed that conducting a thorough assessment of the family's history, dynamics, and current issues. Establishing rapport and building a therapeutic alliance with each family member, some respondents also showed that creating a genogram to visually represents the family structure, relationships, and patterns across generations. From the findings, some respondents showed that insufficient funding and resources for family therapy programs. Lack of access to mental health services and specialized training for social workers. Cultural competence was mentioned by respondents in that most strategies mentioned by respondents in that social workers should be culturally competent and aware of the specific cultural nuances and practices in Buhara sub-county. The study concluded that while reaching the gold standard for effectiveness remains a distant goal for structural–strategic family therapy, this paper offers some evidence about its usefulness for improving individual, dyadic, and family adjustment in families with adolescents with mental health difficulties. The study recommends that family therapy should take a holistic approach by considering the family as a system. This approach is effective in addressing interconnected issues within the family, such as communication patterns, power dynamics, and relational conflicts. Family therapy should help to improve communication patterns within the family. Social workers facilitate open and constructive dialogues, leading to better understanding and resolution of conflicts.